Little Side Holes: Moravian Devotional Cards of the Mid-Eighteenth Century - Atwood, Craig D. (Journal of Moravian history, 2009)
One of the more intriguing types of eighteenth-century Moravian art were small devotional cards. These side-hole cards (Seitenhöhlchenkarten) offer a distinctly Moravian reworking of a medieval iconographic tradition. Most of these cards have verses about the side wound of Jesus written in beautiful calligraphy, sometimes in red and green ink. The most intriguing cards have images of the side wound, sometimes with scenes painted into the wound. Aaron Fogleman offered these pictures as evidence for his thesis that the Moravians viewed Jesus as female and considers them as part of their eroticized devotion to Christ. The author of this essay argues that this is a misinterpretation. These cards were probably used by both children and adults in private devotions and are hardly erotic. Rather, they are visual representations of key elements of Moravian wounds mysticism, especially the concept that all aspects of daily life, even eating and sleeping, should be done in the awareness that one is in the body of Christ.